Pengaruh E-WoM dan Daya Tarik Wisata Terhadap Keputusan Berkunjung Wisatawan Pada Destinasi Wisata Benang Kelambu di Lombok Tengah - Nuraswati; Didy Ika Supryadi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study investigates how online reviews (E-WoM) and tourist attraction appeal influence an individual's decision to visit the Benang Kelambu destination in Central Lombok. We used questionnaires to collect data from 100 previously visited tourists, specifically selected to ensure their relevance to the research. Using multiple linear regression analysis, we found that both factors, E-WoM, and tourist attraction appeal, contribute positively and significantly to tourists' desire to visit. This means that when tourists see positive online reviews or recommendations, and feel the destination offers natural beauty, adequate facilities, and easy access, they are highly likely to decide to visit. In short, tourists come to Benang Kelambu because of the positive information they read online, combined with their direct experience of the natural beauty, sufficient facilities, and ease of reaching the location. These findings are beneficial for Benang Kelambu's management in developing more effective promotional strategies and enhancing the tourist appeal to increase visitor numbers continuously.